(untitled) (Indonesian Health Justice Review, 2025)
The right to health is enshrined in international human rights law, yet its full realization remains a challenge in many countries, including Indonesia. This paper provides a legal analysis of Indonesia’s health policies and evaluates the role of the state in ensuring the right to health for all citizens. By examining constitutional provisions, national health laws, and the implementation of Universal Health Coverage (UHC), the study assesses how effectively Indonesia’s legal framework upholds health rights, particularly for vulnerable populations. Through a review of case law, policy documents, and interviews with legal experts and policymakers, the paper identifies key gaps in the enforcement of health rights, such as access to essential medicines, quality care, and non-discrimination. Findings suggest that while Indonesia has made significant strides in expanding healthcare coverage, particularly with UHC, inequalities persist in healthcare access, especially for marginalized groups. The paper argues that Indonesia’s health policies need to be further aligned with international human rights standards, emphasizing accountability, equity, and the active role of the state in guaranteeing the right to health. Recommendations include strengthening the legal framework for health, improving the enforcement of health rights, and ensuring that the healthcare system is inclusive, affordable, and accessible to all citizens.